Corporate social responsibility and total quality management: As an antecedent of hotel performance - Benavides-Velasco, Carlos Ángel; Quintana-García, Cristina; Marchante-Lara, Macarena (My University, 2014)
Corporate social responsibility (CSR) and total quality management (TQM) are considered potential sources in order to obtain a sustainable competitive advantage. This paper examines how the implementation of both TQM and CSR influences the results of hotels’ stakeholders as an antecedent of business performance. An empirical study of Spanish hotels from the Andalusian region shows that the adoption of such approaches improves the capacity of hotels to create benefits for their stakeholders, and these results have a positive effect on hotel performance. The study also provides evidence of the complementarity of both management philosophies as TQM can enhance the development of CSR.
Keywords: Empresas - Gestión; Calidad total; Sostenibilidad; Calidad; Responsabilidad social corporativa